2021
DOI: 10.7202/1082070ar
|View full text |Cite
|
Sign up to set email alerts
|

Examining Child Maltreatment-Related Investigations of Children from Newcomer and non-Newcomer Households in Ontario, Canada

Abstract: Objectives: The study aims to further the understanding of child welfare involvement with Newcomer families in Ontario, Canada in 2018. This study examines a) the rate and characteristics of child maltreatment-related investigations involving Newcomer families and b) differences in child maltreatment-related investigations between Newcomer and non-Newcomer families. Methods: This study is a secondary data analysis of the Ontario Incidence Study of Reported Child Abuse and Neglect-2018 (OIS-2018). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Prior to the pandemic, it was also reported that disproportionately high numbers of immigrant children and families in large Canadian metropolitan centers encounter child protection services and that these encounters do not always result in improved child and family well-being (Alaggia & Vine, 2013) due to intersecting challenges of poverty, racism, and cultural misunderstanding (Contenta et al, 2014;Fallon et al, 2016). In Ontario, where this study took place, of every 1,000 children in newcomer households, 134 were involved in a child maltreatment-related investigation (Houston et al, 2021). For non-newcomer households, 54 of every 1,000 children were involved in a child maltreatment-related investigation (Houston et al, 2021), a figure indicating that, among families in Canada, newcomers are more likely than non-newcomers to become involved with child welfare services.…”
Section: Immigrant Families and Child Welfarementioning
confidence: 98%
See 1 more Smart Citation
“…Prior to the pandemic, it was also reported that disproportionately high numbers of immigrant children and families in large Canadian metropolitan centers encounter child protection services and that these encounters do not always result in improved child and family well-being (Alaggia & Vine, 2013) due to intersecting challenges of poverty, racism, and cultural misunderstanding (Contenta et al, 2014;Fallon et al, 2016). In Ontario, where this study took place, of every 1,000 children in newcomer households, 134 were involved in a child maltreatment-related investigation (Houston et al, 2021). For non-newcomer households, 54 of every 1,000 children were involved in a child maltreatment-related investigation (Houston et al, 2021), a figure indicating that, among families in Canada, newcomers are more likely than non-newcomers to become involved with child welfare services.…”
Section: Immigrant Families and Child Welfarementioning
confidence: 98%
“…In Ontario, where this study took place, of every 1,000 children in newcomer households, 134 were involved in a child maltreatment-related investigation (Houston et al, 2021). For non-newcomer households, 54 of every 1,000 children were involved in a child maltreatment-related investigation (Houston et al, 2021), a figure indicating that, among families in Canada, newcomers are more likely than non-newcomers to become involved with child welfare services.…”
Section: Immigrant Families and Child Welfarementioning
confidence: 98%